2016
DOI: 10.1111/bjep.12108
|View full text |Cite
|
Sign up to set email alerts
|

Achievement goals and emotions: The mediational roles of perceived progress, control, and value

Abstract: Study findings partially support Linnenbrink and Pintrich's (2002, Educational Psychologist, 37, 69) bidirectional theory of affect while underscoring the potential for indirect effects of goals on emotions through perceived control as proposed by Pekrun (2006, Educational Psychology Review, 18, 315).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
34
1
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(43 citation statements)
references
References 116 publications
5
34
1
3
Order By: Relevance
“…The results of this research are innovative and have shown the moderating effect of perseverance on stress perception. This discovery is in line with the claims of other authors [50,51]; according to them, having the resources to emotionally regulate stress allows a student to have the necessary perseverance to achieve his/her goals.…”
Section: Discussionsupporting
confidence: 83%
“…The results of this research are innovative and have shown the moderating effect of perseverance on stress perception. This discovery is in line with the claims of other authors [50,51]; according to them, having the resources to emotionally regulate stress allows a student to have the necessary perseverance to achieve his/her goals.…”
Section: Discussionsupporting
confidence: 83%
“…External measures evaluated in our study are hypothesized to mediate the impact of achievement emotions on academic performance (Pekrun, b; Pekrun et al, ). There is a growing set of empirical evidence from control‐value theory to support this claim (Burić, ; Hall, Sampasivam, Muis, & Ranellucci, ; Smiley, Buttitta, Chung, Dubon, & Chang, ). The degree of association between the AEQ‐OCHEM and our other study measures support further work to understand more multivariate mediation models.…”
Section: Generative Opportunitiesmentioning
confidence: 99%
“…Various studies have revealed the relationship between learning, motivation, and teaching (Hall et al 2016;Thomas and Muller 2016), and there are many investigations that have focused on studies in the higher education field, as indicated (Angeli dos Santos and Ferreira 2016; Froiland and Worrell 2016). Among the characteristics that make up this instrument is the evaluation of self-regulatory motivation and learning strategies, as well as management of the learning context by university students.…”
Section: Introductionmentioning
confidence: 99%
“…The link between motivation and emotions and learning is closely related. However, as posed by Pekrun (2006) and Hall et al (2016), there are very scarce gauges to explore this relationship. Not much information has been found related to the motivation, learning, and resources in higher education.…”
Section: Introductionmentioning
confidence: 99%